Gamification in mobile ticketing services - Diogo Xambre Gouveia (2022)
Complex transport networks and a lack of integrated options are barriers for using public transport services. Modern mobile ticketing services allow users to travel conveniently and smoothly, thereby enhancing the customer experience. Although some cities implemented mobile ticketing solutions in their public transport network, the adoption of such services appears to have limited success. The use of gamification elements in marketing is an effort to engage users and improve the user experience. Gamification is defined as the implementation of game elements in a non-game context to help users enjoy using a product or service. Despite the potential of this technique, its application in mobile payment solutions is very limited: Also, in order to result in the engagement of the users, this type of application should consider innovations in terms of services offered and business models. This work intends to fill this gap in the literature and apply gamification concepts to mobile ticketing applications for public transport with the ultimate goal of promoting the use of sustainable means of transport, such as public transport, and the use of mobile ticketing solutions. As an illustrative example, the case of the city of Porto, Portugal, which has had a mobile payment application for public transport in use since 2018, was used. The work consisted primarily of a review of the existing literature, which was then divided into three main topics: (i) behavioural change in public transport, (ii) gamification, and (iii) gamification in public transportation and mobile ticketing. This was followed by the design of the solution, based on a user-centred design approach. The first step consisted of understanding the needs and preferences of users regarding the introduction of game elements in the mobile ticketing system, through the use of questionnaires, interviews and focus groups conducted with users of the public transport system in the city of Porto. After gathering user data, and analysing it, a prototype of the mobile ticketing system with gamified elements was developed to satisfy the needs and preferences of the users. Then, the prototype was evaluated by potential users through usability testing. The data obtained in the tests were analysed in order to understand which game elements are most valued and easily apprehended by users in a mobile ticketing application. It is expected that the proposed solution presents advantages both for transport companies and users, making the service more attractive and effective, thereby increasing customer satisfaction and loyalty.